Compressive behavior of small-diameter concrete-filled fiber-reinforced polymer tubes as internal reinforcements. Issue 4 (March 2020) - Fang, Shu; Li, Li-Juan; Jiang, Tao; Fu, Bing
Concrete infilled in a small-diameter fiber-reinforced polymer tube is strongly confined, thus having a high compressive strength and excellent deformability. Such a feature is exploited in the development of two types of high-performance hybrid members at Guangdong University of Technology, China, by incorporating small-diameter (30 to 60 mm) concrete-filled fiber-reinforced polymer tubes as internal reinforcements. Understanding the compressive behavior of small-diameter concrete-filled fiber-reinforced polymer tubes is essential to understanding the behavior of the proposed hybrid members and the development of their design approaches. This article therefore presents a systematic study on the axial compressive behavior of small-diameter concrete-filled fiber-reinforced polymer tubes with the test parameters being the thickness, diameter, and fiber type of fiber-reinforced polymer tubes and concrete strength. The test results show that the tested small-diameter concrete-filled fiber-reinforced polymer tubes have a compressive strength and an ultimate axial strain of up to 267 MPa and 10.3%, which are, respectively, about 6 and 34 times that of the corresponding unconfined specimens, demonstrating the great potential of small-diameter concrete-filled fiber-reinforced polymer tubes as internal reinforcements for use in high-performance hybrid members. The applicability of three widely accepted stress–strain models developed based on test results of fiber-reinforced polymer-confined concrete cylinders with a diameter of 150 mm or above is also examined. It is shown that the three models tend to predict a steeper second portion of stress–strain responses than the test results, revealing the need of a tailored stress–strain model for small-diameter concrete-filled fiber-reinforced polymer tubes.